HUBUNGAN PENGALAMAN MENGAJAR DAN PERSEPSI GURU TENTANG KEPEMIMPINAN KEPALA SEKOLAH DENGAN KINERJA GURU SMK SWASTA SE-KECAMATAN BOYOLALI TAHUN AJARAN 2011/2012 - Kurniawan, Nanang (Jurnal Nosel, 2013)
The purpose of this research is to know: (1) The Correlation Teaching Experience with Performance of Teacher?s;(2) The Correlation The Teacher's Perception in Respect of Principal's Leadership with Teachers Performance;(3) The Correlation Teaching Experience and Teacher?s Perceptions In Respect Of Principal Leadership Simultaneously with Teacher?s Performance;(4) A Stronger Correlation between The Teaching Experience and Teacher?s Perceptions of Principal Leadership with Teacher?s Performance. The population of this research were the teacher?s of private vocational school as much as 199 teacher?s in Boyolali district. The sample of this research were 60 teacher?s and respondents for the trial were 35 teacher?s. Sampling study uses proportional random sampling technique. Data collection uses questionnaire for variable of teaching experience, teacher?s perceptions of principal?s leadership and teacher?s performance. To test the validity, the reseach used product moment approach. While, Alpha formula was used to test the reliability of the instrument. Analysis of data was used analytical of Pearson Product Moment correlation techniques. The reseach needs to be done requirements analysis testing before, namely: (1) Normality Test, (2) Linearity Test, (3) Multicollinearity Test. The results show: (1) There is a positive and significant correlation of teaching experience with teacher performance. It is based on the results of the first hypothesis test with the product moment correlation analysis rcount> rtable (0.551> 0.254) at the 5% significance level, (2) There is a positive and significant correlation of in respect of principal leadership and teacher?s performance. It is based on hypothesis test results both with the product moment correlation analysis rcount> rtable (0.495> 0.254) at the 5% significance level, (3) There is a positive correlation of teaching experience and teacher?s perceptions in respect of principal leadership and teacher?s performance. Based on the results of hypothesis testing with multiple correlation analysis of the obtained results Fcount> Ftable (24.495> 3.159) at the 5% significance level, (4) The effective contribution of 26.1% of teaching experience and teacher?s perceptions of principal leadership 20.1%. This results indicate that the association of teaching experience and teacher?s performance is stronger than the correlation the teacher?s perception of the principal's leadership and teacher?s performance.